Electroanalytical techniques for investigating biofilms: Applications in biosensing and biomolecular interfacing - Shetti N.P.; Malode S.J.; Roy S.; Chandra P.; Reddy K.R.; Chatterjee S. (My University, 2025)
Biofilms, which are widespread in the natural world and have a complex composition, have demonstrated significant performance capabilities in the field of biosensing diagnostics. Biofilms provide an excellent surface for both living and nonliving microbes to develop, thus allowing different microorganisms to become viable and later utilized in biosensor detection strategies. Biofilms formed by bacteria have created numerous problems in areas such as the medical, food, and water industries. A thorough analysis of biofilm is difficult because these collections of microorganisms present concerns in both the microbiological and hygiene fields. As a result, these methods are aimed at analyzing biofilm formations and their progress at diverse phases. Performing research on biofilm employs both qualitative and quantitative techniques to understand their properties. Electrochemically active biofilms, which are environmentally friendly, help transfer electrons to generate conductivity and to measure the growth kinetics of biofilms. The electrochemical sensors not only cooperate to detect and characterize bacterial biofilms, but also to reduce their electrical impedance by increasing the electrochemical signals. The charge transfer resistance and capacity of biofilm growth can also be successfully detected. This chapter highlights the advantages, limits, and analysis techniques to assist the researcher in assay selection. © 2020 Elsevier Inc.